Understanding Media Consumption of Electronic Sports through Spectator Motivation, Using Three Different Segmentation Approaches: The Levels of Addiction, Passion, and Fan Identification - Chulhwan Choi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Electronic sports (eSports), or competitive video gaming, is a type of sport that has recently expanded its horizon from being a participatory sport to a spectator sport fueled by its wide popularity. In this regard, it is necessary to investigate why fans enjoy this new sports genre as a spectator sport. This study examines motivations of eSports spectators in different segments to gain a better understanding of the behaviors of this growing population. Specifically, this study aimed to (a) investigate eSports spectators' motivations to discover the motives for their attachment to eSports, using eleven different factors, and (b) explore differences in motivations among levels of addiction, fan identification, and passion. An analysis of 368 eSports fans showed that they valued the Achievement and Economics factors most in watching eSports. They even experienced a sense of achievement and a certain pecuniary advantage that real sports spectators experience. In addition, the Escape factor was identified as being the most important factor in explaining a passion for eSports-watching. This study also discovered significant differences between the eleven spectator motives, demonstrating the effectiveness of segmentation analysis in investigating the behaviors of sports fans. In particular, the Economics and Escape factors revealed meaningful differences between groups for all segments. This study showed that eSports spectators watch this new type of sports based on motivations that are similar to those of existing sports fans; furthermore, it identified significant differences in spectator motivations depending on their level of involvement in eSports.